Bank maturity, income diversification, and bank stability - Tariq, Waqas; Usman, Muhammad; Tariq, Adeel; Rashid, Robina; Yin, Junming; Memon, Mumtaz Ali; Ashfaq, Muhammad (Journal of Business Economics and Management, 2021)
The purpose of this research is to examine the influence of bank life cycle or bank maturity on income diversification (ID) and stability. In addition, this research investigates the ID relationship with bank stability. Drawing on the dynamic resource-based view and modern portfolio theory, this research examines the influence of a paramount internal factor i.e. bank life cycle or bank maturity on income diversification (ID) and stability consequence. Data were collected from the Pakistani’s commercial banks’ financial statements over the period 2005 to 2019. This research relied on the fixed effect and generalized method of moments (GMM) model to empirically test the proposed relationships. Core findings of the research reveal that bank maturity leads to enhanced ID and ID strongly influences the bank stability consequence, moreover, research findings are robust to use different measures of bank stability and GMM estimation techniques. To the authors’ best knowledge, this research is the first to report specific evidence about bank maturity as an internal driver of income diversification and stability and advances the literature seeking to understand the determinants of ID. This research also shows managers to recognize the importance of internal drivers to diversify effectively into non-interest income, and how such an effective ID translates into stability consequence.